Coronary Angiographic Profile of Patients with Acute Non ST-Segment Elevation Myocardial Infarction with Chronic Kidney Disease (University Heart Journal, 2016)
Background: Nearly 40% of patients presenting with Non ST-Segment Elevation Myocardial Infarction (NSTEMI) have Chronic Kidney Disease (CKD). CKD is a powerful predictor of adverse events among NSTEMI patients. CKD is associated with a high prevalence of obstructive coronary artery disease.Objectives: The purpose of the present study was to evaluate the severity of coronary artery disease in patients with Chronic Kidney Disease presenting with Non ST-Segment Elevation Myocardial Infarction. Methods: In this prospective observational study a total of 128 patients with NSTEMI were enrolled. They were divided equally in group I (NSTEMI with CKD) and group II (NSTEMI with normal renal function) on the basis of estimated glomerular filtration rate. Patients were considered to have CKD if he/she had documented history of CKD or estimated glomerular filtration rate